Porous carbon material as well as preparation method and application thereof
Through the coordination of metal molten salt and pore-forming agent, the pore structure of porous carbon materials is regulated, and the problem of difficult control of pore structure in the existing technology is solved, the electrochemical performance and safety of sodium ion batteries are improved, and industrial production is realized feasibility.
Patent Information
- Application Number
- CN202411322618.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing porous carbon material preparation methods are complex in technology and difficult to control the pore structure, resulting in insufficient electrochemical performance and safety of sodium ion batteries and are not suitable for large-scale industrial production.
The combination of metal molten salt and pore-forming agent is used to regulate the pore structure of porous carbon materials through pre-firing and carbonization processes, making them regular and uniform, simplify the process and reduce costs, and is suitable for industrial production.
It has achieved improved controllability of porous carbon materials, improved the electrochemical performance and safety of sodium ion batteries, and simplified the preparation process, reduced production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119143128A_ABST
Abstract
Description
[0001] This application is a divisional application of patent application No. 2022116026561 (the filing date of the original application is December 13, 2022, and the name of the invention is A porous carbon material, its preparation method and application). Technical Field
[0002] The invention belongs to the technical field of batteries and relates to a porous carbon material and a preparation method and application thereof. Background Art
[0003] Lithium-ion batteries are widely used in consumer electronics, electric vehicles, energy storage and other fields due to their advantages such as high energy density and long cycle life. However, due to the scarcity of lithium mineral resources and other related issues, lithium resources are currently in short supply and prices remain high, which has certain restrictions on large-scale applications in some markets. Compared with lithium resources, sodium resources are very abundant. In the scenario of large-scale application, sodium batteries have no obvious resource constraints. After subsequent industrialization and cost reduction, the cost of sodium batteries will be lower. In addition, sodium batteries can work normally in the temperature range of -40℃ to 80℃, and the capacity retention rate is close to 90% in an environment of -20℃. The high and low temperature performance is better than other secondary batteries. At the same time, the internal resistance of sodium batteries is higher than that of lithium batteries, and the instantaneous heat generation is less in the case of short circuit, the temperature rise is lower, the thermal runaway temperature is higher than that of lithium batteries, and it has higher safety.
[0004] Porous carbon materials have the characteristics of large specific surface area, high electrical conductivity and high porosity, and have certain applications in high-rate lithium-ion batteries. For sodium-ion batteries with relatively large ionic radius, porous carbon materials have greater advantages when used as negative electrode materials. Among them, the regularization and uniformity of the pore structure of porous carbon materials will affect the electrochemical performance of sodium batteries, especially the safety and consistency of sodium batteries. In the prior art, conventional preparation methods of porous carbon materials mainly include activation method and template method, among which the template method specifically includes soft template method, hard template method and dual template method, etc. Although the porous material can have good structural controllability, the preparation process is complicated and cumbersome, and is not suitable for large-scale industrial production.
[0005] The activation preparation method specifically includes chemical activation method, catalytic activation method, polymer mixed carbonization and biomass carbonization activation, etc. For example, CN 102897746A discloses a method for preparing a porous carbon material and a porous carbon material prepared according to the method. The method includes using polytetraphenylmethane having a porous organic skeleton material as a raw material, and using alkali metal hydroxides such as KOH, NaOH and CsOH as activators, mixing the two in a certain proportion, and activating under a nitrogen flow to obtain a porous carbon material. However, the activation method often produces disordered porous carbon materials, and it is difficult to control the pore shape and pore size, and the pore structure has poor controllability.
[0006] Based on the above research, it is necessary to provide a method for preparing porous carbon materials. The preparation method has a simple process, low cost, and can directionally modify the pore structure to obtain an ordered porous carbon material with regular pore structure and high uniformity, thereby improving the electrochemical performance of sodium ion batteries. Summary of the invention
[0007] The purpose of the present invention is to provide a porous carbon material and a preparation method and application thereof. The preparation method achieves the regulation of the pores of the porous carbon material by using a metal molten salt and a pore-forming agent, so that the pore structure is regularized and highly uniform, thereby achieving controllable adjustment of the pore structure, and has low cost, simple process, and can be industrialized and mass-produced.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0010] (1) mixing a carbon source, a metal molten salt and a pore-forming agent, and then pre-calcining to obtain a pre-calcined material;
[0011] (2) Carbonizing and washing the pre-sintered material in step (1) to obtain the porous carbon material.
[0012] The preparation method of the present invention can obtain a porous carbon material with regular pores and high uniformity by adding a pore-forming agent of a metal molten salt, wherein the melting effect of the metal molten salt at high temperature can make the porous carbon material and the pores tend to a two-dimensional structure, and can be removed in the subsequent washing process, successfully modifying the pore structure, and at the same time, when combined with a pore-forming agent, the porous carbon material can contain multiple types of pores through the combined effect of the two, such as micropores, mesopores and macropores at the same time; and, since it is first pre-calcined and then carbonized, the pre-calcination stage can first remove impurities and pre-form pores, thereby improving the material purity while improving the regularity of the pores; in addition, the preparation process of the present invention is simple, except that the washing process is in the liquid phase, the rest are solid phase processes, thereby reducing the preparation cost, enabling the preparation method to be industrially produced on a large scale, and the cost controllability during industrial preparation is high.
[0013] Preferably, the mass ratio of the carbon source, the metal molten salt and the pore-forming agent in step (1) is 10:x:y, wherein 1<x≤50, for example, it can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 8≤x≤50.
[0014] Among them, 0.5<y≤15, for example, it can be 0.5, 1, 3, 5, 7, 9, 11, 13 or 15, but it is not limited to the listed values. Other unlisted values within the numerical range are also applicable, and preferably 5≤y≤15.
[0015] The regularity and uniformity of the pores can only be guaranteed when the contents of the carbon source, metal molten salt and pore-forming agent described in the present invention are within a specific range. If the content of the metal molten salt is too high, the prepared carbon material will have a two-dimensional sheet structure without a three-dimensional pore structure; if the content of the pore-forming agent is too high, the three-dimensional pore structure will be highly disordered and the pores will be uneven.
[0016] Preferably, the metal molten salt in step (1) comprises any one of metal halides, hydroxides, sulfates, nitrates or carbonates, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of metal halides and hydroxides, a combination of sulfates and nitrates, or a combination of carbonates and sulfates, preferably nitrates and / or sulfates, and more preferably nitrates.
[0017] The type of the metal molten salt described in the present invention is preferably nitrate and / or sulfate. Since the metal molten salt can directly achieve doping with the N element when it is a nitrate, and can linearly achieve doping with the S element when it is a sulfate, doping and preparation are simplified to one process, and the doped porous carbon material can improve the electrochemical performance of the battery.
[0018] Preferably, the metal ions in the metal molten salt in step (1) include Li + 、Na + Mg 2+ 、Al 3+ , K + or Ca 2+ Any one or a combination of at least two of the following, typical but non-limiting combinations include Li + and Na + A combination of Mg 2+ and Al 3+ combination.
[0019] Preferably, the pre-burning temperature in step (1) is 250-600°C, for example, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, and the pre-burning time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the pre-burning in step (1) is carried out under low pressure conditions, or in a protective gas, preferably under low pressure conditions.
[0021] Preferably, the pressure of the low pressure condition is 100-5000Pa, for example, it can be 100Pa, 500Pa, 1000Pa, 2000Pa, 3000Pa, 4000Pa or 5000Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Since the pore-forming agent decomposes under high temperature conditions to generate gas, thereby forming pores, and impurities are also gasified, pre-firing under low pressure conditions is conducive to the removal of gas during the pre-firing process, thereby facilitating pre-firing and impurity removal.
[0023] Preferably, the mixing in step (1) comprises premixing the carbon source and the metal molten salt by ball milling, grinding them, and then adding a pore-forming agent for grinding.
[0024] Preferably, the grinding is performed under the circulation of cooling water.
[0025] Preferably, the grinding temperature is 5-30°C, for example, 5°C, 10°C, 15°C, 20°C, 25°C or 30°C, 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] If the temperature is too high during the grinding process, the material will melt, making it impossible to mix the raw materials evenly. If the grinding temperature is too low, it is not conducive to mixing. Therefore, the present invention uses the circulation of cooling water to take away the heat generated during the grinding process and ensure the temperature during the grinding process. Among them, the cooling water does not enter the grinding system, and the grinding process is still solid phase grinding.
[0027] Preferably, the equipment used for the grinding includes any one of a planetary ball mill, a vibration ball mill, a rotary mill or a disc mill.
[0028] Preferably, the rotation speed of the ball milling premix is 150-250rpm, for example, 150rpm, 200rpm or 250rpm, and the time is 3-10min, for example, 3min, 5min, 7min, 9min or 10min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the ball mill premix is ground at a speed of 400-600 rpm, for example, 400 rpm, 500 rpm or 600 rpm, for 2-5 h, for example, 2 h, 3 h, 4 h or 5 h, and then the pore-forming agent is added at a speed of 400-600 rpm, for example, 400 rpm, 500 rpm or 600 rpm, and ground for 3-6 h, for example, 3 h, 4 h, 5 h or 6 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the pore-forming agent in step (1) comprises any one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, polyvinyl alcohol, methacrylic acid or urea, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ammonium carbonate and ammonium bicarbonate, or a combination of ammonium chloride and ammonium carbonate.
[0031] Preferably, the carbon source in step (1) comprises an organic carbon source.
[0032] Preferably, the organic carbon source comprises any one of petroleum asphalt, coal tar, phenolic resin, coconut shell, rice husk, glucose or sucrose, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of petroleum asphalt and coal tar, or a combination of glucose and sucrose.
[0033] Preferably, the pre-burnt material in step (1) is also crushed before carbonization.
[0034] The crushing followed by carbonization after pre-sintering described in the present invention is beneficial to the escape of gas, and is beneficial to the metal molten salt to two-dimensionalize the material and the pores, thereby facilitating the generation of various types of pores, and is also beneficial to improving the regularity and uniformity of the pores.
[0035] Preferably, the particle size D50 of the crushed pre-sintered material is 3-10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the crushing equipment includes any one of a universal crusher, a jet mill or a planetary ball mill.
[0037] Preferably, the carbonization temperature in step (2) is 1050-1400°C, for example, 1050°C, 1100°C, 1200°C, 1300°C or 1400°C, and the time is 2-10h, for example, 2h, 4h, 6h, 8h or 10h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the carbonization in step (2) is carried out under low pressure conditions, or in a protective gas, preferably under low pressure conditions.
[0039] Preferably, the pressure of the low pressure condition is 100-5000Pa, for example, it can be 100Pa, 500Pa, 1000Pa, 2000Pa, 3000Pa, 4000Pa or 5000Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the protective gas includes any one of nitrogen, argon, helium or krypton, or a combination of at least two of them.
[0041] Preferably, the washing liquid used in step (2) comprises deionized water.
[0042] Preferably, the washing in step (2) is performed 2-4 times, for example, 2 times, 3 times or 4 times.
[0043] Preferably, after the washing in step (2), a drying step is also performed.
[0044] Preferably, the drying equipment includes any one of a vacuum oven, a forced air drying oven, a microwave drying oven or an infrared drying oven.
[0045] Preferably, the drying temperature is 80-120°C, for example, 80°C, 100°C, 110°C or 120°C, and the drying time is 5-12h, for example, 5h, 7h, 9h, 11h or 12h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] As a preferred technical solution of the preparation method, the preparation method comprises the following steps:
[0047] (1) firstly premix the carbon source and the metal molten salt by ball milling, then grind, then add a pore-forming agent and grind, and then pre-sinter at a temperature of 250-600° C. for 1-6 hours under a low pressure condition of 100-5000 Pa to obtain a pre-sintered material;
[0048] The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:x:y, wherein 0<x≤50, 0<y≤15;
[0049] The grinding temperature is 5-30°C and is carried out under the circulation of cooling water;
[0050] (2) The pre-sintered material of step (1) is crushed to a particle size D50 of 3-10 μm, and then carbonized at a temperature of 1050-1400° C. for 2-10 h under a pressure of 100-5000 Pa, and then washed with deionized water for 2-4 times, and then dried to obtain the porous carbon material.
[0051] In a second aspect, the present invention provides a porous carbon material, which is prepared by the preparation method described in the first aspect.
[0052] In a third aspect, the present invention provides a sodium ion battery, comprising the porous carbon material as described in the second aspect.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) The present invention ensures the purity of the porous carbon material by combining a pore-forming agent and a metal molten salt, and then pre-calcining and then carbonizing, effectively modifying the pores in a directional manner, and obtaining an ordered porous carbon material with regular pores and high uniformity, thereby improving its performance when used as a battery material;
[0055] (2) The overall preparation process of the present invention is simple, and except for the post-treatment washing process which is in the liquid phase, the rest are solid phase processes, which can be mass-produced industrially, and have low cost and high cost controllability. At the same time, the preparation method of the present invention can integrate preparation and doping by selecting specific metal molten salts to obtain a doped porous carbon material with ordered pores, which not only further simplifies the preparation process, but also further improves the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The full range pore size distribution diagram of the porous carbon materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 3 of the present invention;
[0057] Figure 2 This is the first charge and discharge curve of the porous carbon material obtained in Example 1 of the present invention after being prepared into a battery. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] Example 1
[0060] This embodiment provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0061] (1) The carbon source and the metal molten salt were pre-milled in a planetary ball mill at a speed of 150 rpm for 10 min, then ground in a rotary grinder at a speed of 500 rpm for 3 h, and then a pore-forming agent was added and ground at a speed of 400 rpm for 3 h. The obtained ground material was pre-calcined at a temperature of 550° C. for 3 h under a low pressure of 1000 Pa to obtain a pre-calcined material;
[0062] The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:44:6, the carbon source is coal tar pitch with a mass of 5 g, the metal molten salt is sodium chloride with a mass of 22 g, and the pore-forming agent is ammonium bicarbonate with a mass of 3 g;
[0063] The grinding temperature is 10°C and is carried out under the circulation of cooling water;
[0064] (2) crushing the pre-sintered material in step (1) to a particle size D50 of 7.8 μm in a universal grinder, and then carbonizing it at a temperature of 1300° C. for 4 h in a nitrogen atmosphere, and then washing it with deionized water for 3 times, and then drying it in a vacuum drying oven at 120° C. for 10 h to obtain the porous carbon material;
[0065] The full range pore size distribution diagram of the porous carbon material obtained in this example is as follows Figure 1 The first charge and discharge curve of the porous carbon material after being prepared into a battery is shown in Figure 2 shown.
[0066] Example 2
[0067] This embodiment provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0068] (1) The carbon source and the metal molten salt were first pre-mixed by ball milling at a speed of 200 rpm in a planetary ball mill for 5 min, then ground in a disc mill at a speed of 400 rpm for 5 h, and then a pore-forming agent was added and ground at a speed of 450 rpm for 6 h. The obtained ground material was pre-calcined at a temperature of 600° C. for 5 h in an argon atmosphere to obtain a pre-calcined material;
[0069] The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:8:5, the carbon source is phenolic resin with a mass of 10 g, the metal molten salt is potassium nitrate with a mass of 8 g, and the pore-forming agent is methacrylic acid with a mass of 5 g;
[0070] The grinding temperature is 5°C and is carried out under the circulation of cooling water;
[0071] (2) crushing the pre-sintered material in step (1) to a particle size D50 of 5.4 μm in a planetary ball mill, and then carbonizing it at a temperature of 1350° C. for 2 h in an argon atmosphere, and then washing it with deionized water for 4 times, and then drying it in a forced air drying oven at 80° C. for 8 h to obtain the porous carbon material;
[0072] The full range pore size distribution diagram of the porous carbon material obtained in this example is as follows Figure 1 shown.
[0073] Example 3
[0074] This embodiment provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0075] (1) The carbon source and the metal molten salt were pre-milled in a planetary ball mill at a speed of 250 rpm for 3 min, then ground in a rotary grinder at a speed of 600 rpm for 2 h, and then a pore-forming agent was added and ground at a speed of 600 rpm for 3 h. The obtained ground material was pre-calcined at a temperature of 250° C. for 6 h under a low pressure of 5000 Pa to obtain a pre-calcined material;
[0076] The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:50:15, the carbon source is coal tar pitch with a mass of 5 g, the metal molten salt is sodium chloride with a mass of 25 g, and the pore-forming agent is ammonium bicarbonate with a mass of 7.5 g;
[0077] The grinding temperature is 30°C and is carried out under the circulation of cooling water;
[0078] (2) The pre-burned material in step (1) is crushed in a universal crusher to a particle size D50 of 10 μm, and then carbonized at a temperature of 1050° C. for 10 h under a low pressure of 100 Pa, and then washed twice with deionized water, and then dried in a vacuum drying oven at 120° C. for 5 h to obtain the porous carbon material.
[0079] Example 4
[0080] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1, except that in step (1), the masses of the molten metal salt and the pore-forming agent are changed so that the mass ratio of the carbon source, the molten metal salt and the pore-forming agent is 10:2:1.
[0081] Example 5
[0082] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1, except that the mass of the metal molten salt in step (1) is changed so that the mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:55:6.
[0083] Example 6
[0084] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1 except that the mass of the pore-forming agent in step (1) is changed so that the mass ratio of the carbon source, the molten metal salt and the pore-forming agent is 10:44:20.
[0085] Example 7
[0086] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1 except that the metal molten salt in step (1) is sodium nitrate.
[0087] Example 8
[0088] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1 except that the metal molten salt in step (1) is sodium sulfate.
[0089] Example 9
[0090] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1 except that the pre-calcination in step (1) is performed under a nitrogen atmosphere.
[0091] Example 10
[0092] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1, except that the grinding in step (1) is not performed under the circulation of cooling water to change the grinding temperature accordingly.
[0093] Embodiment 11
[0094] This embodiment provides a method for preparing a porous carbon material. The preparation method is the same as that of Embodiment 1 except that in step (1), the pre-burned material is not crushed, but the material is crushed to a particle size D50 of 7.8 μm after carbonization.
[0095] Comparative Example 1
[0096] This comparative example provides a method for preparing a porous carbon material, which is the same as Example 1 except that the carbon source, the metal molten salt and the pore-forming agent in the mass ratio of 10:44:6 in step (1) are replaced by sucrose and magnesium sulfate in the mass ratio of 15:100, the grinding process is changed accordingly, and the D50 of the pre-sintered material is 6.7 μm;
[0097] The full range pore size distribution diagram of the porous carbon material obtained in this comparative example is as follows Figure 1 shown.
[0098] Comparative Example 2
[0099] This comparative example provides a method for preparing a porous carbon material. The preparation method is the same as Example 1, except that the carbon source, metal molten salt and pore-forming agent in a mass ratio of 10:44:6 in step (1) are replaced by phenolic resin and potassium carbonate in a mass ratio of 30:80, the grinding process is changed accordingly and the D50 of the pre-burned material is 6.5 μm.
[0100] Comparative Example 3
[0101] This comparative example provides a method for preparing a porous carbon material, which is the same as Example 1 except that the mass of the metal molten salt in step (1) is replaced by ammonium bicarbonate as a pore-forming agent;
[0102] The full range pore size distribution diagram of the porous carbon material obtained in this comparative example is as follows Figure 1 shown.
[0103] Comparative Example 4
[0104] This comparative example provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0105] The carbon source and the metal molten salt are pre-mixed by ball milling at a speed of 150 rpm for 10 minutes in a planetary ball mill, and then ground at a speed of 500 rpm for 3 hours in a rotary grinder, and then a pore-forming agent is added and ground at a speed of 400 rpm for 3 hours. The obtained ground material is carbonized at a temperature of 1300° C. for 4 hours in a nitrogen atmosphere, and then washed with deionized water for 3 times, and then dried at 120° C. for 10 hours in a vacuum drying oven, and then crushed in a universal grinder to a particle size D50 of 7.8 μm to obtain the porous carbon material;
[0106] The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:44:6, the carbon source is coal tar pitch with a mass of 5 g, the metal molten salt is sodium chloride with a mass of 22 g, and the pore-forming agent is ammonium bicarbonate with a mass of 3 g.
[0107] The porous carbon materials obtained in the above embodiments and comparative examples were tested for specific surface area using the Quantachrome NOVA-e analyzer of the United States, using the principle of low-temperature adsorption of N2 by liquid nitrogen; 1% Nonidet p40 dispersant and the substance to be tested were ultrasonically subjected to particle size analysis for 5 minutes using the Malvern MS3000 particle size analyzer of the United Kingdom; and the ASAP2460 fully automatic aperture instrument of McMerritt was used for analysis, and the full range pore size distribution and specific surface area of the material were obtained using the nitrogen adsorption test isotherm. The test results are shown in Table 1.
[0108] Then, the porous carbon material, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) obtained in the above embodiments and comparative examples were slurried, coated, cut into pieces, and baked in a mass ratio of 9.3:0.15:0.25:0.3 to obtain a negative electrode sheet, and the negative electrode sheet and the sodium sheet were assembled into a CR2430 button battery, wherein the electrolyte used was 1 mol / L NaPF6 ethylene carbonate (EC) and diethyl carbonate (DEC) solution. After the assembly was completed, it was stored in a constant temperature box at 60°C for 6 hours, and then the electrochemical performance test was carried out at a current density of 0.1C. The obtained first discharge specific capacity and first coulomb efficiency are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] In the table, micropores refer to pores with a pore diameter less than 2 nm, mesopores refer to pores with a pore diameter between 2 nm and 50 nm, and macropores refer to pores with a pore diameter greater than 50 nm.
[0113] From Table 1 we can see that:
[0114] (1) The porous carbon material obtained by the present invention has a variety of pores and a high uniformity in pore size distribution, so the prepared battery has excellent performance; it can be seen from Example 1 and Comparative Examples 1-3 that only by mixing a metal molten salt with a carbon source to prepare a porous carbon material, or only by mixing a pore-forming agent with a carbon source to prepare a porous carbon material, the combination of the metal molten salt and the pore-forming agent cannot be brought into play, and not only the uniformity of the pore size distribution is reduced, but also the corresponding battery performance is reduced; it can be seen from Example 1 and Comparative Example 4 that the present invention first performs pre-burning and crushing and then carbonization, which is more conducive to pore formation, gas removal, and at the same time, it is conducive to improving the uniformity of pore size distribution and battery performance.
[0115] (2) It can be seen from Examples 1 and 5-6 that when the content of the metal molten salt and the pore-forming agent is too much and is not within the scope of the present application, the regularity and uniformity of the pores cannot be guaranteed, and the corresponding electrochemical performance decreases; It can be seen from Examples 1 and 7-8 that when the metal molten salt is nitrate and sulfate, it can play the role of doping N and S, and accordingly can improve the electrochemical performance of the battery; It can be seen from Examples 1 and 9-10 that the present invention preferably performs pre-burning under low pressure conditions, and at the same time, the grinding temperature can be reduced under the action of cooling water to ensure the mixing effect, thereby further improving the uniformity of pore distribution and the electrochemical performance of the battery; It can be seen from Examples 1 and 11 that crushing and then carbonizing after pre-burning can improve the pore-forming effect.
[0116] In summary, the present invention provides a porous carbon material and a preparation method and application thereof. The preparation method achieves the regulation of the pores of the porous carbon material by adopting a metal molten salt and a pore-forming agent, so that the pore structure is regularized and highly uniform, thereby achieving controllable adjustment of the pore structure. In addition, the preparation method has low cost, simple process, and can be industrially mass-produced.
[0117] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A porous carbon material, characterized in that: The pores of the porous carbon material include micropores and mesopores; The pore size of the micropores is less than 2 nm, and the pore size of the mesopores is between 2 nm and 50 nm.
2. The porous carbon material according to claim 1, characterized in that The pores of the porous carbon material further include macropores, and the pore diameter of the macropores is greater than 50 nm; Preferably, among the holes, micropores account for 12-41%, preferably 22-41%; Preferably, the proportion of mesopores in the pores is 27-76%, preferably 49-76%; Preferably, among the holes, the proportion of macropores is 1-61%, preferably 1-29%.
3. The porous carbon material according to claim 1 or 2, characterized in that: The specific surface area of the porous carbon material is 249-3170 m 2 / g, preferably 648-2644m 2 / g; Preferably, the particle size D50 of the porous carbon material is 5.4-8.4 μm, preferably 5.4-7.8 μm.
4. The porous carbon material according to any one of claims 1 to 3, characterized in that: The pores of the porous carbon material are regular, uniform and orderly; Preferably, the pores of the porous carbon material are a two-dimensional structure; Preferably, the porous carbon material is doped with N and / or S.
5. A method for preparing a porous carbon material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a carbon source, a metal molten salt and a pore-forming agent, and then pre-calcining to obtain a pre-calcined material; (2) Carbonizing and washing the pre-sintered material in step (1) to obtain the porous carbon material.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the carbon source, the metal molten salt and the pore-forming agent in step (1) is 10:x:y, wherein 1<x≤50, 0.5<y≤15; Preferably, the metal molten salt in step (1) comprises any one or a combination of at least two of metal halides, hydroxides, sulfates, nitrates or carbonates, preferably nitrates and / or sulfates, and more preferably nitrates; Preferably, the metal ions in the metal molten salt in step (1) include Li + 、Na + Mg 2+ 、Al 3+ , K + or Ca 2+ Any one or a combination of at least two of the following: Preferably, the pre-calcination temperature in step (1) is 250-600° C. and the time is 1-6 hours; Preferably, the pre-burning in step (1) is carried out under low pressure conditions, or in a protective gas, preferably under low pressure conditions; Preferably, the pressure of the low pressure condition is 100-5000Pa.
7. The preparation method according to claim 5 or 6, characterized in that: The mixing in step (1) comprises first premixing the carbon source and the metal molten salt by ball milling, then grinding, and then adding a pore-forming agent for grinding; Preferably, the grinding is carried out under the circulation of cooling water; Preferably, the grinding temperature is 5-30°C; Preferably, the equipment used for the grinding includes any one of a planetary ball mill, a vibration ball mill, a rotary mill or a disc mill.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The pore-forming agent in step (1) includes any one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, polyvinyl alcohol, methacrylic acid or urea, or a combination of at least two thereof; Preferably, the carbon source in step (1) comprises an organic carbon source; Preferably, the organic carbon source comprises any one or a combination of at least two of petroleum asphalt, coal asphalt, phenolic resin, coconut shell, rice shell, glucose or sucrose; Preferably, the pre-burned material in step (1) is also subjected to a crushing step before carbonization; Preferably, the particle size D50 of the crushed pre-sintered material is 3-10 μm.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The carbonization temperature in step (2) is 1050-1400° C. and the time is 2-10 h; Preferably, the carbonization in step (2) is carried out under low pressure conditions or in a protective gas; Preferably, the pressure of the low pressure condition is 100-5000Pa; Preferably, the washing liquid used in step (2) comprises deionized water; Preferably, the washing times in step (2) are 2-4 times; Preferably, after the washing in step (2), a drying step is also performed.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The preparation method comprises the following steps: (1) firstly premix the carbon source and the metal molten salt by ball milling, then grind, then add a pore-forming agent and grind, and then pre-sinter at a temperature of 250-600° C. for 1-6 hours under a low pressure condition of 100-5000 Pa to obtain a pre-sintered material; The mass ratio of the carbon source, the metal molten salt and the pore-forming agent is 10:x:y, wherein 1<x≤50, 0.5<y≤15; The grinding temperature is 5-30°C and is carried out under the circulation of cooling water; (2) The pre-sintered material of step (1) is crushed to a particle size D50 of 3-10 μm, and then carbonized at a temperature of 1050-1400° C. for 2-10 h under a pressure of 100-5000 Pa, and then washed with deionized water for 2-4 times, and then dried to obtain the porous carbon material.
